Metode Pelaksanaan Rigid Pavement Proyek Tol Probolinggo - Banyuwangi Paket 1 - Muhammad Daniel M; Subchan Ali Zainal A; Yerry Kahaditu F (Jurnal Penelitian Rumpun Ilmu Teknik, 2025)
Roads are land transportation media which include parts of the road, complementary buildings and equipment that are useful for traffic, these facilities can stand above or below the surface of water and land. In daily activities, the need for roads is unavoidable, starting from the need to deliver goods and the human transportation medium itself. The Probowangi Highway is a road infrastructure development project initiated as part of the government's efforts to increase regional connectivity and improve transportation access between regions. This writing explains the pavement implementation method used, namely rigid pavement, because the advantage of pavement is that it is better in load distribution. In implementing this project, there are 2 methods, namely using struss screet concrete wacker and Wirtgen SP64. So there are many things that need to be considered in its implementation, especially in locations that use single wiremesh and double wiremesh.